ENHANCING POST-PANDEMIC LEARNING AT THE PRIMARY EDUCATION LEVEL: AN IN-DEPTH EXAMINATION OF MULTIMEDIA-INFUSED PEDAGOGY'S EFFICACY - Yuarini Wahyu Pertiwi; Akhmadi; Zulvia Trinova; Aan Suryana; Sitti Nur Alam (CV. ADIBA AISHA AMIRA, 2023)
This study discussed the effectiveness of using multimedia in children's learning after the pandemic. To prove which zodiac sign is effective in multimedia learning, we have conducted a series of scientific publication studies on several books and other scientific literature that actively discuss issues related to the effectiveness of multimedia in learning Covid paste. The study involved a data coding system, evaluation, and conclusion to get a valid answer to this hypothesis—the data search we did electronically on several kinds of literature released ten years ago. After a series of studies and discussion of the results, we can conclude that multimedia-based learning is one of the innovative learning because it involves a variety of relevant media for elementary school learning for elementary school children. After all, learning has been disrupted. Thus, this discussion received essential and valuable input for further studies